Enhancement of growth and survival rates in asian redtail catfish (Hemibagrus nemurus CV) larvae with probiotic soaking technique - Sukendi Sukendi; Manda Putra Ridwan; Efriyeldi; Andriani Delvira; Cahya Fitri Sabilah Triani (BIO Web of Conferences)
One of the freshwater fish commodity has a high economic value is Asian redtail catfish. However, the Asian redtail catfish growth relatively slow between larvae stage until fry stage. The solutions for this problem is giving probiotics that can be increase the growth of fish larvae. The aimed to analyse the effect of immersion on Asian redtail catfish larvae in probiotics to improve growth and survival rate. This study was conducted between May until July 2024 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine, Riau University. This study used a completely randomized design with immersion treatment using the probiotics trademark raja siam at different dose, namely 0 ml/L, 1.5 ml/L, 2.0 ml/L, and 2.5 ml/L. Based the results of study shown that the best dose of immersion on Asian redtail catfish larvae using probiotics was in 2.5 ml/L, the absolute weight growth at 9.7818 g, absolute length growth at 9.03 cm, specific growth rate at 11.91%/day, cannibalism type A, B were 2.00%, 0.00%, cannibalism index 2.00%, normal mortality 5.33% and survival rate 92.67%.